Valoración económica del secuestro del CO2 en las parcelas vii y viii del arboretum el “huayo” del CIEFOR, Puerto Almendra, Iquitos, 2021 - Doza Pinedo, Ricardo Ernesto (2023)
The present study allows us to know how to assess the sequestration of CO2 in natural forest, in plots VII and VIII of the “Huayo” Arboretum of CIEFOR, Puerto Almendra, Iquitos, 2021, of the Faculty of Forestry Sciences of the National University of the Amazon. Peruvian, quantitative type and non-experimental design. In plot VII there is a total of 341 259,34 kg of biomass and 170,63 tC, and in plot VIII there is a total of 363 470,18 kg of biomass and 181,74 tnC. Plot VII sequesters 625,58 tnCO2, whose valuation is USD 51 189,42; and in plot VIII, it sequesters 666,30 tnCO2 whose valuation is USD 54 521,08. To determine the hypothesis, the Kolmogorov-Sminorv normality test was performed, which indicated that it does not have a normal distribution, therefore, the non-parametric Kruskal-Wallis test has a p-value of 0.035 lower than the level of significance of 0.05, indicating that there is a difference between the economic valuation of CO2 sequestration in plots VII and VIII of the Arboretum. The “El Huayo” aboretum belongs to a mid-terrace forest as the plant formation that sequesters and stores high levels of CO2 and carbon in its trees, giving greater importance to conservation and good management.